EKSPLORASI METODE STORYTELLING DALAM PEMBELAJARAN AGAMA ISLAM SEBAGAI SARANA UNTUK MEMOTIVASI DAN MENINGKATKAN IMAJINASI SISWA DI SMA N 3 MUARA MUNTAI N 3 MUARA MUNTAI - Muhammad junaidi (UNISAN JURNAL, 2024)
The use of storytelling methods in Islamic teaching at SMA N 3 Muara Muntai has become the focus of research to understand its impact on student motivation and imagination. This research explores the effectiveness of storytelling methods in increasing student engagement and enriching their imagination. Through a qualitative approach, data was collected through observation, interviews and document analysis from students and teachers involved in learning Islamic Religion. The research results showed that the use of the storytelling method succeeded in increasing student motivation, with a higher level of involvement in learning. Students show greater enthusiasm in following religious stories and participate actively in discussions and related activities. Apart from that, the storytelling method has also been proven to enrich students’ imaginations. Religious stories awaken students’ imagination, allowing them to imagine the experiences in the stories more realistically. This helps students understand religious concepts more concretely and creatively, increasing their understanding of the teachings of the Islamic religion. These findings highlight the importance of a creative approach in learning Islam, with the storytelling method as one strategy to increase student interest, involvement and understanding.